A Bécsi Megállapodás - 2001. június 29. : Jugoszlávia szétesésének pillanata - Szávai, Ferenc (Közép-Európai Közlemények, 2013)
The 20th century has not increased with too many new states; however new states have arisen, or we could met phenomenon called state failure. The former socialist integration, the Yugoslavian Socialist Republic disintegrated alongside much other integration; this phenomenon has not been cleared for long, the experts thought to discover the case of dismembratio (disintegration) in it; it is proved by the document ratified and signed by the five succession state in 29th June, 2001. The antecedent was the international contract “The Vienna Convention on Succession of States in Respect of State Property, Archives and Debts” from 1983; it realized the fortune of state property remained in abroad, buildings of foreign affairs or the gold reserve of the Central Bank. Besides, by the same principle, it divided on a percentage basis of the public debt, but also dealt with intellectual wealth. The core of this study was provided by the analysis of the documents but the secession of Montenegro and Kosovo was in relation with the disintegration process as well. Montenegro was founded by the secession which occurred in a peaceful way. The independence of Montenegro inured in June 3rd 2006 and was approved by the European Union in June 12th 2006. Finally, Kosovo announced its intention to become independent in February 17th 2008, thus it decided on separation in accordance to international law.